Correlation of IgA Accumulation with Clinical Findings in Children with Henoch-Schoenlein Nephritis - Belde Kasap; Afşin Kundak; Mehmet Türkmen; Alper Soylu; Sülen Sarıoğlu; Salih Kavukçu (Archives of Rheumatology, 2008)
Objective: Henoch-Schoenlein purpura (HSN), an IgA-mediated disease is the most common form of systemic vasculitis seen in childhood and long-term prognosis depends on renal involvement. We aimed to investigate the influence of renal IgA accumulation on clinical and histopathological findings in children with HSN. Materials and Methods: Seventeen patients who were diagnosed as HSN based on renal biopsy were included in the study. The clinical assessment at baseline and last visit were done according to a classification adapted from that of Goldstein et al and renal histopathological changes were graded according to the classification of International Study of Kidney Disease in Childhood. IgA accumulation was quantified as +1 to +4. Based on this, patients were divided into group 1 (+1 or +2 accumulation) and group 2 (+3 or +4 accumulation). All parameters were compared between the groups. Results: There was no significant difference between the groups with respect to clinical findings and histopathological changes. The amount of IgA accumulation was not correlated with clinical or histopathological status. Conclusion: The amount of renal IgA deposition is not associated with clinical or histological findings in our sample. These results need to be confirmed in larger samples. (Rheumatism 2008; 23: 114-7)